Solve for p 7(2p+1)-4(3p+2)=0

Math
7(2p+1)-4(3p+2)=0
Simplify 7(2p+1)-4(3p+2).
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
7(2p)+7⋅1-4(3p+2)=0
Multiply 2 by 7.
14p+7⋅1-4(3p+2)=0
Multiply 7 by 1.
14p+7-4(3p+2)=0
Apply the distributive property.
14p+7-4(3p)-4⋅2=0
Multiply 3 by -4.
14p+7-12p-4⋅2=0
Multiply -4 by 2.
14p+7-12p-8=0
14p+7-12p-8=0
Simplify by adding terms.
Tap for more steps…
Subtract 12p from 14p.
2p+7-8=0
Subtract 8 from 7.
2p-1=0
2p-1=0
2p-1=0
Add 1 to both sides of the equation.
2p=1
Divide each term by 2 and simplify.
Tap for more steps…
Divide each term in 2p=1 by 2.
2p2=12
Cancel the common factor of 2.
Tap for more steps…
Cancel the common factor.
2p2=12
Divide p by 1.
p=12
p=12
p=12
The result can be shown in multiple forms.
Exact Form:
p=12
Decimal Form:
p=0.5
Solve for p 7(2p+1)-4(3p+2)=0

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top